The organization of manufacture of precast concrete building system "CUB 3V - V. A. Popov; V. A. Kazakov; A. F. Andruchenkov; N. S. Volovnik (Вестник СибАДИ)
The article presents the results of a patent search for the manufacture of prefabricated technology bezrigelnyh carcasses of residential buildings. The advantages of the technology of installation buildings "KUB 3V» progressive construction system. Proposed for use in the Siberian region of the various options Works on manufacturing of construction of the system. We consider the construction of a new plant for the production of products, proposed modernization of existing plants. The basis of the patented manufacturing technology is taken beltline SL-7. Achieved eco-nomic justification of the proposed options and ways to implement the proposed marked-acceptable solutions.